Evaluasi Usability Pada Aplikasi SiPaduko dengan Menggunakan Metode Usability Testing - Muhammad Zulfi Tisna Tama; Warcita Warcita; Yovi Pratama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
SiPaduko (Jambi City Population Administration Service Information System) is a service system application that aims to provide easy population management services to the people of Jambi City which will be used in 2021. However, the presence of this application in the community not only provides convenience, but there are also several obstacles faced by the people of Jambi City in operating the application, so it is necessary to evaluate the Usability of the SiPaduko application so that later the application can be developed even better. In this study, a Usability evaluation was carried out using the Usability Testing method. Based on the results of the analysis of the 5 variables used, there are 4 independent variables namely Learnability, Efficiency, Memorability, and Satisfaction which have a partial or individual effect significantly on the dependent variable, namely Usability . In addition, there is 1 independent variable, namely Errors that have a partial or independent effect with no significant effect on the dependent variable, namely Usability. Then, to simultaneously or together the 5 independent variables have a significant effect on the dependent variable. Furthermore, the results of measuring the efficiency of using the application obtained an efficiency value with an average percentage of 96.66% and a usage time efficiency value of 0.007073 per second. In this study , the tools used to analyze are SPSS (Statistical Product and Service Solutions)